Type-2 Fuzzy Logic Controlled Adjustable Step-Size LMS Algorithm for DSTATCOM - Vivekanand, Ganji; K. Chandra sekhar, Dr; Suresh, D (International Journal of Engineering and Technology, 2018)
In this paper, voltage source converter is utilized as a distributed static compensator (DSTATCOM). The voltage source converter has advantages of lower capacitor size and reduced switching losses. The DSTATCOM is used to elimination of harmonics and reactive power of the nonlinear load. The reference currents of DSTATCOM estimated with type-2 fuzzy logic control step-size updated least mean square algorithm.Conventionally, the proportional integral controller is used for control of dc link voltage and current of DSTATCOM. The proportional controller requires in detailed mathematical modeling of the overall system and it is tedious process. Â To overcome aforementioned task interval type-2 fuzzy logic controller (IT2FLC) applied for a voltage source converter based DSTATCOM. The proposed IT2FLC is utilized to regulate the DC voltage as well as update the step size of the algorithm to improve the performances of the DSTATCOM. The overall system of DSTATCOM including T2FLC implemented in MATLAB/Simulink. The simulated response of DSTATCOM found to be improved and better than the conventional LMS algorithm controller.Â Â